Moisture-permeable layered composite fabric and preparation method thereof
By using antibacterial polyvinylidene fluoride fiber membrane and electrospinning technology in waterproof and moisture-permeable composite fabrics, combining epoxy resin/water-based polyurethane composite materials and β-cyclodextrin/polytetrahydrofuran ether glycol composites, a three-layer structure moisture-permeable layered composite fabric is formed, which solves the problem of insufficient antibacterial and moisture-permeable properties of the existing fabrics, and achieves excellent water-resistant moisture-permeable properties and mechanical properties.
Patent Information
- Application Number
- CN202510131937.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-06
- Publication Date
- 2025-03-07
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing waterproof and moisture-permeable composite fabrics lack antibacterial properties, and due to the direct coating form selected for the adhesive layer material, the moisture-permeable performance of the fabric is affected, resulting in a lower moisture-permeable amount.
Antibacterial polyvinylidene fluoride fiber membrane is used as the inner layer fabric, and intermediate layer/inner layer composite fabric is prepared through electrospinning technology, combining epoxy resin/water-based polyurethane composite material and β-cyclodextrin/polytetrahydrofuran ether glycol composite to form a three-layer structure moisture-permeable layer composite fabric.
It achieves excellent waterproof and moisture permeability of the fabric, enhances mechanical properties and antibacterial properties, and improves moisture permeability.
Smart Images

Figure CN119567676A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of multi-layer fabrics, and in particular to a moisture-permeable layered composite fabric and a preparation method thereof. Background Art
[0002] Waterproof and breathable fabrics combine waterproof and breathable properties, not only preventing external liquids such as rain and snow from soaking in, but also allowing perspiration to escape from the body through the fabric, creating a sense of comfort. Fabric waterproofness refers to its ability to resist the penetration of liquid water from one side to the other, while fabric breathability refers to the ability of vaporous water to pass through the fabric, referred to as moisture permeability or vapor permeability. Microporous membranes utilize a microporous barrier principle, limiting the pore size of the microporous membrane to a value between water vapor and the minimum water droplet diameter. The microporous membrane is then combined with ordinary fabrics through coating or lamination, imparting excellent waterproof and breathable properties to the layered fabric.
[0003] Existing technologies, such as Chinese patent application CN109591406A, disclose a waterproof and breathable composite fabric. The method comprises coating a coating agent having waterproof and breathable functions on the surface of a fabric substrate to form a waterproof and breathable coating, and then coating the coating with an adhesive and then covering the coating with a TPU film to obtain a waterproof and breathable composite fabric. However, the waterproof and breathable fabric obtained by this method lacks antibacterial properties, and since the adhesive layer material is directly coated, the adhesive is a conventional commercially available product, which will affect the breathable properties of the layered composite fabric, resulting in a low breathable capacity of the composite fabric, thereby limiting the application of the fabric. Summary of the Invention
[0004] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a moisture-permeable layered composite fabric and a preparation method thereof, wherein the layered composite fabric has excellent waterproof and moisture-permeable properties, and good mechanical properties and antibacterial properties.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows: A method for preparing a moisture-permeable layered composite fabric comprises the following steps: Step (1), stirring and mixing polyvinylidene fluoride, an antibacterial agent, and N,N-dimethylacetamide to obtain a spinning solution for the inner layer material; After electrospinning the inner layer material spinning solution, an antibacterial polyvinylidene fluoride fiber membrane is obtained, and then dried to obtain the inner layer fabric; The antibacterial agent is prepared by the following steps: S11, mixing γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water, and ethanol, adding a regulator to adjust the pH value, adding nanosilver, reacting, and filtering after the reaction, washing, and drying to obtain epoxy nanosilver; S12, dissolving polyvinyl alcohol and dimethyl sulfoxide, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and sodium hydroxide aqueous solution, reacting, adding ethanol after the reaction is completed, filtering, and drying to obtain modified polyvinyl alcohol; S13, uniformly mixing the modified polyvinyl alcohol and water, adding a regulator to adjust the pH value, adding n-butyraldehyde dropwise, reacting after the addition is complete, adding a neutralizing agent to neutralize to neutrality after the reaction is complete, filtering, washing, and drying to obtain modified polyvinyl butyral; S14, mixing modified polyvinyl butyral, ethanol, and nitric acid aqueous solution, adding ceric ammonium nitrate and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, reacting, filtering, washing, and drying after the reaction to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex to obtain a spinning solution of the intermediate layer material, and electrospinning the spinning solution of the intermediate layer material to obtain an intermediate layer / inner layer composite fabric; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dihydroxymethylpropionic acid, stannous isooctanoate, and N,N-dimethylformamide are mixed, 1,4-butanediol is added, and the mixture is reacted. After the reaction is completed, epoxy resin E-44 is added and the reaction is continued. After the reaction is completed, a diluent is added to dilute the mixture to obtain an epoxy resin / waterborne polyurethane composite material. The β-cyclodextrin / polytetramethylene ether glycol complex is prepared by the following steps: β-cyclodextrin and N,N-dimethylacetamide are mixed, polytetramethylene glycol is added, and the mixture is stirred. After the treatment, the mixture is dried, washed, and filtered to obtain a β-cyclodextrin / polytetramethylene glycol complex. Step (3): Lay the middle layer / inner layer composite fabric flat and air dry until the solvent evaporates completely, cover the outer layer fabric on the side with the middle layer, and heat press to obtain a moisture-permeable layered composite fabric.
[0006] Preferably, in step (1), the mass ratio of polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide is 10-13:0.8-1.2:100; and the thickness of the inner layer fabric is 30-40 μm.
[0007] Preferably, in step (1), the electrospinning operation comprises: injecting the inner layer material spinning solution into a syringe of the electrospinning equipment, covering the roller with glossy paper as a receiving screen, spinning the inner layer material spinning solution through the electrospinning instrument at room temperature, the propulsion speed of the inner layer material spinning solution is 3-4 ml / h, the spinning voltage is 30-35 kV, and the receiving distance is 15-20 cm.
[0008] Preferably, when preparing the antibacterial agent in step (1), in S11: the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water, ethanol, and nanosilver is 0.6-0.8:100-150:80-90:10; and the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 40-50°C for 3-5h.
[0009] Preferably, the regulator comprises a 0.5 mol / L aqueous solution of hydrogen chloride.
[0010] Preferably, when preparing the antibacterial agent in step (1), in S12, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver, and sodium hydroxide aqueous solution is 100:180-200:1.8-2:1-1.5:8-10, and the sodium hydroxide aqueous solution is a 10wt% sodium hydroxide aqueous solution; and the reaction conditions are: reaction at a temperature of 55-65°C for 4-5h.
[0011] Preferably, when preparing the antibacterial agent in step (1), in S13: the mass ratio of modified polyvinyl alcohol, water, and n-butyraldehyde is 75-80:750-800:48-52; the dropping conditions of n-butyraldehyde are: dropping for 10-20 minutes at a pH value of 2-3 and a temperature of 15-20°C; the reaction conditions are: react at room temperature for 2-3 hours, and after the reaction is completed, heat the mixture to 45-50°C at a heating rate of 8-10°C / h, and continue the reaction for 1-2 hours.
[0012] Preferably, the regulator comprises a 1 mol / L aqueous solution of hydrogen chloride; and the neutralizer comprises a 5 wt % aqueous solution of sodium hydroxide.
[0013] Preferably, when preparing the antibacterial agent in step (1), in S14: the mass ratio of modified polyvinyl butyral, ethanol, nitric acid aqueous solution, ceric ammonium nitrate, and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt is 8-10:8.5-9:18-22:0.3-0.35:1-1.2, and the nitric acid aqueous solution is 0.01 mol / L nitric acid aqueous solution; the reaction conditions are: reaction in a nitrogen atmosphere at a temperature of 25-30°C for 20-24 hours.
[0014] Preferably, in step (2), the mass ratio of the epoxy resin / aqueous polyurethane composite material to the β-cyclodextrin / polytetramethylene ether glycol composite material is 100:2-6; the electrospinning operation comprises: injecting the spinning solution of the intermediate layer material into a syringe of the electrospinning device, using the inner layer fabric as a receiving screen, spinning the intermediate layer material through the electrospinning instrument at room temperature, the propulsion speed of the spinning solution is 1.0-1.5 ml / h, the spinning voltage is 15-20 kV, and the receiving distance is 15-20 cm.
[0015] Preferably, in step (2): in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 20-30 μm.
[0016] Preferably, when preparing the epoxy resin / waterborne polyurethane composite material in step (2), the mass ratio of polytetramethylene ether glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dihydroxymethylpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 is 8-10:8-10:10-12:0.5-0.55:0.3-0.5:10-15:1.8-2:1-1.2; the mixing conditions are: mixing for 20-30 minutes at a temperature of 70-80°C in a nitrogen atmosphere; the reaction conditions are: reacting for 1-2 hours at a temperature of 75-85°C in a nitrogen atmosphere; and the continued reaction conditions are: continuing the reaction for 1-2 hours at a temperature of 70-80°C in a nitrogen atmosphere; and the solid content of the epoxy resin / waterborne polyurethane composite material is 10-13%.
[0017] Preferably, the diluent comprises toluene.
[0018] Preferably, when preparing the β-cyclodextrin / polytetramethylene ether glycol complex in step (2), the mass ratio of β-cyclodextrin to N,N-dimethylacetamide is 1:4; the molar ratio of β-cyclodextrin to polytetramethylene ether glycol is 1:0.5-1; and the stirring treatment conditions are: stirring at room temperature for 1-2 hours.
[0019] Preferably, the polytetramethylene ether glycol used in preparing the β-cyclodextrin / polytetramethylene ether glycol complex is the same as the polytetramethylene ether glycol used in preparing the epoxy resin / waterborne polyurethane composite material.
[0020] Preferably, in step (3), the hot pressing conditions are: hot pressing at a pressure of 2-3 MPa and a temperature of 70-80° C. for 3-4 minutes.
[0021] Preferably, in step (3): the outer fabric is made of a material having a gram weight of 120-160 g / m 2The polyester fabric is prepared after waterproof finishing. The finishing operation includes: impregnating the polyester fabric with a waterproof finishing agent at a bath ratio of 1:20-30, an immersion time of 20-30 minutes, one immersion and one rolling, and a rolling rate of 60-70%. After impregnation, drying at a temperature of 90-100°C for 3-5 minutes and baking at a temperature of 150-160°C for 2-3 minutes to obtain an outer layer fabric. The waterproof finishing agent is prepared by mixing a water repellent, a penetrant, a cross-linking agent, a softener, and water in a mass ratio of 5-6:0.1-0.15:1.5-2:8-10:100.
[0022] Preferably, a moisture permeable layered composite fabric is prepared using the method for preparing a moisture permeable layered composite fabric as described above.
[0023] Compared with the prior art, the present invention has the following beneficial effects: The present invention uses an antibacterial polyvinylidene fluoride fiber membrane as the inner layer fabric; an epoxy resin / aqueous polyurethane composite material and a β-cyclodextrin / polytetramethylene ether glycol complex are mixed to obtain a spinning solution of the middle layer material, which is electrospun on the inner layer fabric to obtain a middle layer / inner layer composite fabric; the outer layer fabric and the middle layer / inner layer composite fabric are hot-pressed to obtain a moisture-permeable layered composite fabric; the layered composite fabric has excellent waterproof and moisture-permeable properties, as well as good mechanical properties and antibacterial properties.
[0024] The invention uses epoxy nanosilver prepared by surface modification of an epoxy silane coupling agent as an inorganic antibacterial carrier, adds polyvinyl alcohol and 3-chloro-2-hydroxypropyltrimethylammonium chloride, and performs an etherification reaction under the catalysis of a sodium hydroxide aqueous solution. The obtained modified polyvinyl alcohol contains inorganic antibacterial agent nanosilver and organic antibacterial group quaternary ammonium salt and has better antibacterial performance. The modified polyvinyl alcohol is reacted with n-butyraldehyde for acetalization to obtain modified polyvinyl butyral. Under the action of a catalyst, ceric ammonium nitrate is used to introduce a sulfonic acid-containing compound into the modified polyvinyl butyral through a free radical polymerization reaction initiated by redox. 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt of betaine antibacterial group is used to obtain an antibacterial agent with multiple antibacterial components including nanosilver, quaternary ammonium salt, and sulfobetaine. Due to the synergistic effect of each component on the antibacterial effect, the obtained antibacterial agent has excellent antibacterial properties. After mixing it with polyvinylidene fluoride for electrostatic spinning, the obtained inner layer fabric has good mechanical properties and antibacterial properties. In addition, since the fiber membrane formed by electrostatic spinning has the characteristics of fine fiber diameter, small pore size, and high porosity, the inner layer fabric has excellent moisture permeability. The present invention adds 2,2-dihydroxymethylpropionic acid and polyethylene glycol during the preparation process of polyurethane to introduce carboxylic acid ion hydrophilic groups and polyethylene glycol hydrophilic non-ionic structures to form a waterborne polyurethane prepolymer. Epoxy resin is used as one of the chain extender raw materials, and the hydroxyl groups of the epoxy resin react with the isocyanate groups of the waterborne polyurethane prepolymer to introduce epoxy groups into the waterborne polyurethane matrix to obtain an epoxy resin / waterborne polyurethane composite material. The epoxy resin is then compounded with a β-cyclodextrin / polytetramethylene ether glycol complex, and electrostatic spinning is performed on an inner layer fabric to obtain an intermediate layer / inner layer composite fabric. Among them, epoxy resin / waterborne polyurethane composite materials have good hydrophilicity due to the presence of hydrophilic groups. The intermediate layer material prepared with it as raw material can absorb and release water molecules, improving the moisture conductivity and moisture permeability of the layered composite fabric. Its epoxy group can enhance the adhesion of the intermediate layer material. After lamination with the inner and outer layers of fabric, the layered composite fabric has better mechanical properties. The β-cyclodextrin / polytetramethylene ether glycol complex is prepared by combining β-cyclodextrin and polytetramethylene ether glycol. The lipophilic dimethylene group of polytetramethylene ether glycol can form a strong interaction with the hydrophobic inner cavity of β-cyclodextrin, and the hydroxyl group can interact with the hydrophilic external hydroxyl group of β-cyclodextrin. Therefore, polytetramethylene ether glycol has a good modification effect on β-cyclodextrin. The prepared β-cyclodextrin / polytetramethylene ether glycol complex has good compatibility with the epoxy resin / waterborne polyurethane composite material. In addition, the hydroxyl group and ether oxygen bond of the β-cyclodextrin / polytetramethylene ether glycol complex can also provide more channels and adsorption points for water molecules to enter the intermediate layer material, further improving the hydrophilicity, moisture conductivity and moisture permeability of the intermediate layer material. The present invention performs hydrophobic finishing on the outer layer fabric and then hot presses it with the middle layer / inner layer composite fabric to form a layered composite fabric with a three-layer structure of waterproof and moisture permeable / moisture conductive / moisture permeable, which has excellent waterproof and moisture permeable properties, good mechanical properties and antibacterial properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a process flow chart for preparing a moisture-permeable layered composite fabric in the present invention; Figure 2 Schematic diagram of the structure of the moisture-permeable layered composite fabric prepared in the present invention; Figure 3 1 is a bar graph showing the moisture permeability of the layered composite fabrics prepared in the examples and comparative examples of the present invention in performance tests; In the picture: 1. Outer fabric; 2. Middle fabric; 3. Inner fabric. DETAILED DESCRIPTION
[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Example
[0027] This embodiment discloses a method for preparing a moisture-permeable layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 10:0.8:100 at room temperature for 10 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3 ml / h, the spinning voltage was 30 kV, and the receiving distance was 15 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 40 ° C for 3 hours to obtain an inner layer fabric with a thickness of 40 μm. The antibacterial agent is prepared by the following steps: S11, γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water, and ethanol were mixed, 0.5 mol / L aqueous hydrogen chloride solution was added dropwise to adjust the pH value to 4, nanosilver was added, the mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water, ethanol, and nanosilver was 0.7:130:85:10, and the mixture was reacted at 45°C for 4 hours. After the reaction was completed, the filter cake was filtered and washed with ethanol 6 times the mass of the filter cake, and dried at 55°C for 22 hours to obtain epoxy nanosilver; S12, mixing and dissolving polyvinyl alcohol and dimethyl sulfoxide at 90° C., adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and 10 wt % sodium hydroxide aqueous solution, wherein the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and 10 wt % sodium hydroxide aqueous solution is 100:180:1.8:1:8, and reacting at 55° C. for 5 h. After the reaction is completed, a crude reaction product is obtained, ethanol 5 times the mass of the crude reaction product is added, and the mixture is filtered, and the filter cake is taken and dried at 50° C. for 24 h to obtain modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at 90° C., mixing evenly, and cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 2, adding n-butyraldehyde dropwise at 15° C. for 10 min, reacting at room temperature for 2 h, heating to 45° C. at a heating rate of 8° C. / h after the reaction, and continuing the reaction for 2 h. After the reaction, adding 5 wt % aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, washing with water 5 times the mass of the filter cake, and drying at 50° C. for 24 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 75:750:48; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ceric ammonium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added. The mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ceric ammonium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 8: 8.5: 18: 0.3: 1. The mixture was reacted in a nitrogen atmosphere at a temperature of 25 ° C for 24 hours. After the reaction was completed, the filter was filtered, the filter cake was taken, 5 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 50 ° C for 24 hours to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:2 at a temperature of 60° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.0 ml / h, the spinning voltage being 15 kV, the receiving distance being 15 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 30 μm; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 70°C for 30 minutes, 1,4-butanediol was added, and the mixture was reacted at 75°C for 2 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 70°C for 2 hours. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 10%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 8:8:10:0.5:0.3:10:1.8:1; The β-cyclodextrin / polytetramethylene ether glycol complex is prepared by the following steps: β-cyclodextrin and N,N-dimethylacetamide were mixed in a mass ratio of 1:4, polytetramethylene glycol was added, and the molar ratio of β-cyclodextrin to polytetramethylene glycol was 1:0.8. The mixture was stirred at room temperature for 1.5 hours. After the treatment, the mixture was dried at 85°C for 9 hours to obtain a crude product. The crude product was washed three times with ethanol 8 times the mass of the crude product, and filtered to obtain a β-cyclodextrin / polytetramethylene glycol complex. The polytetramethylene ether glycol used in preparing the β-cyclodextrin / polytetramethylene ether glycol composite is the same as the polytetramethylene ether glycol used in preparing the epoxy resin / waterborne polyurethane composite material; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent evaporates completely, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 2 MPa and a temperature of 70°C for 4 minutes to obtain a moisture-permeable layered composite fabric; Among them, the outer fabric is made of 140g / m 2 The polyester fabric is prepared after waterproof finishing; the finishing operation includes: impregnating the polyester fabric with a waterproof finishing agent at a bath ratio of 1:20, an immersion time of 20 minutes, one immersion and one rolling, and a rolling rate of 64%; after impregnation, drying at 95°C for 4 minutes and baking at 155°C for 2 minutes to obtain an outer layer fabric; the waterproof finishing agent is prepared by mixing a water repellent, a penetrant, a cross-linking agent, a softener, and water in a mass ratio of 5.5:0.12:1.5:8:100.
[0028] Example 2 This embodiment discloses a method for preparing a moisture-permeable layered composite fabric, comprising the following steps: Step (1), mixing polyvinylidene fluoride, an antibacterial agent, and N,N-dimethylacetamide at a mass ratio of 11:0.9:100 at room temperature for 11 hours to obtain a spinning solution for the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3.5 ml / h, the spinning voltage was 30 kV, and the receiving distance was 18 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 45 ° C for 2.5 hours to obtain an inner layer fabric with a thickness of 40 μm. The antibacterial agent is prepared by the following steps: S11, the preparation of epoxy nanosilver is the same as that in Example 1; S12, polyvinyl alcohol and dimethyl sulfoxide were mixed and dissolved at a temperature of 90° C., 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and a 10 wt % aqueous sodium hydroxide solution were added, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and the 10 wt % aqueous sodium hydroxide solution being 100:185:1.85:1.2:9, and the mixture was reacted at a temperature of 60° C. for 4.5 h. After the reaction was completed, a crude reaction product was obtained, ethanol in an amount of 6 times the mass of the crude reaction product was added, the mixture was filtered, a filter cake was taken, and it was dried at a temperature of 55° C. for 20 h to obtain a modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at a temperature of 90° C., mixing evenly, and then cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 2, adding n-butyraldehyde dropwise at a temperature of 18° C. for 15 min, and reacting at room temperature for 2.5 h. After the reaction is completed, heating to 45° C. at a heating rate of 8° C. / h, and continuing the reaction for 1.5 h. After the reaction is completed, adding 5 wt % aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, adding water 6 times the mass of the filter cake to wash, and drying at 55° C. for 22 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 76:760:49; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ceric ammonium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added. The mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ceric ammonium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 8.5:8.6:19:0.32:1.05. The mixture was reacted in a nitrogen atmosphere at a temperature of 25 ° C for 22 hours. After the reaction was completed, the filter was filtered, the filter cake was taken, 8 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 55 ° C for 22 hours to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:3 at a temperature of 60° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.3 ml / h, the spinning voltage being 18 kV, the receiving distance being 18 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 30 μm; The preparation of β-cyclodextrin / polytetramethylene ether glycol complex is the same as that in Example 1; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 75°C for 25 minutes, 1,4-butanediol was added, and the mixture was reacted at 80°C for 1.5 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 75°C for 1.5 hours. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 11%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 8.5:8.5:10.5:0.52:0.35:12:1.85:1.05; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent evaporates completely, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 2.5 MPa and a temperature of 75°C for 3.5 minutes to obtain a moisture-permeable layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0029] Example 3 This embodiment discloses a method for preparing a moisture-permeable layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 12:1:100 at room temperature for 11 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3.5 ml / h, the spinning voltage was 33 kV, and the receiving distance was 18 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained. It was vacuum dried at 45 ° C for 2.5 hours to obtain an inner layer fabric with a thickness of 35 μm. The antibacterial agent is prepared by the following steps: S11, the preparation of epoxy nanosilver is the same as that in Example 1; S12, polyvinyl alcohol and dimethyl sulfoxide were mixed and dissolved at a temperature of 92° C., 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and a 10 wt % aqueous sodium hydroxide solution were added, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and the 10 wt % aqueous sodium hydroxide solution being 100:190:1.9:1.3:9, and the mixture was reacted at a temperature of 60° C. for 4.5 h. After the reaction was completed, a crude reaction product was obtained, ethanol in an amount of 6 times the mass of the crude reaction product was added, the mixture was filtered, a filter cake was taken, and it was dried at a temperature of 55° C. for 20 h to obtain a modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at 92° C., mixing evenly and then cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 2.5, adding n-butyraldehyde dropwise at 18° C. for 15 min, reacting at room temperature for 2.5 h, heating to 45° C. at a heating rate of 8° C. / h after the reaction, and continuing the reaction for 1.5 h. After the reaction is completed, adding 5 wt % aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55° C. for 22 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 78:780:50; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ceric ammonium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added. The mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ceric ammonium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 9: 8.8: 20: 0.32: 1.1. The mixture was reacted in a nitrogen atmosphere at a temperature of 28 ° C for 22 hours. After the reaction was completed, the filter was filtered, the filter cake was taken, 8 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 55 ° C for 22 hours to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:4 at a temperature of 63° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.3 ml / h, the spinning voltage being 18 kV, the receiving distance being 18 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 25 μm; The preparation of β-cyclodextrin / polytetramethylene ether glycol complex is the same as that in Example 1; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 75°C for 25 minutes, 1,4-butanediol was added, and the mixture was reacted at 80°C for 1.5 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 75°C for 1.5 hours. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 12%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 9:9:11:0.53:0.4:13:1.9:1.1; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent evaporates completely, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 2.5 MPa and a temperature of 75°C for 3.5 minutes to obtain a moisture-permeable layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0030] Example 4 This embodiment discloses a method for preparing a moisture-permeable layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 12.5:1.1:100 at room temperature for 11 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3.5 ml / h, the spinning voltage was 33 kV, and the receiving distance was 18 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 45 ° C for 2.5 hours to obtain an inner layer fabric with a thickness of 30 μm. The antibacterial agent is prepared by the following steps: S11, the preparation of epoxy nanosilver is the same as that in Example 1; S12, polyvinyl alcohol and dimethyl sulfoxide were mixed and dissolved at a temperature of 95° C., 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and a 10 wt % aqueous sodium hydroxide solution were added, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and the 10 wt % aqueous sodium hydroxide solution being 100:195:1.95:1.4:9.5, and the mixture was reacted at a temperature of 60° C. for 4.5 h. After the reaction was completed, a crude reaction product was obtained, ethanol in an amount of 6 times the mass of the crude reaction product was added, the mixture was filtered, a filter cake was taken, and it was dried at a temperature of 55° C. for 20 h to obtain a modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at 95°C, mixing evenly and then cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 3, adding n-butyraldehyde dropwise at 18°C for 15 min, reacting at room temperature for 2.5 h, heating to 50°C at a heating rate of 10°C / h after the reaction, and continuing the reaction for 1.5 h. After the reaction is completed, adding 5 wt% aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, adding water 6 times the mass of the filter cake for washing, and drying at 55°C for 22 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 79:790:51; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ceric ammonium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added. The mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ceric ammonium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 9.5:8.9:21:0.33:1.15. The mixture was reacted at 30 ° C for 22 hours in a nitrogen atmosphere. After the reaction was completed, the filter was filtered, the filter cake was taken, 8 times the mass of the filter cake was added for washing, and the filter cake was dried at 55 ° C for 22 hours to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / waterborne polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:5 at a temperature of 65° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.3 ml / h, the spinning voltage being 18 kV, the receiving distance being 18 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 20 μm; The preparation of β-cyclodextrin / polytetramethylene ether glycol complex is the same as that in Example 1; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 75°C for 25 minutes, 1,4-butanediol was added, and the mixture was reacted at 80°C for 1.5 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 75°C for 1.5 hours. After the reaction was completed, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 13%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 9.5:9.5:11.5:0.54:0.45:14:1.95:1.15; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent evaporates completely, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 2.5 MPa and a temperature of 75°C for 3.5 minutes to obtain a moisture-permeable layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0031] Example 5 This embodiment discloses a method for preparing a moisture-permeable layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 13:1.2:100 at room temperature for 12 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 4 ml / h, the spinning voltage was 35 kV, and the receiving distance was 20 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 50 ° C for 2 hours to obtain an inner layer fabric with a thickness of 30 μm. The antibacterial agent is prepared by the following steps: S11, the preparation of epoxy nanosilver is the same as that in Example 1; S12, polyvinyl alcohol and dimethyl sulfoxide were mixed and dissolved at a temperature of 95° C., 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and a 10 wt % aqueous sodium hydroxide solution were added, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and the 10 wt % aqueous sodium hydroxide solution being 100:200:2:1.5:10, and the mixture was reacted at a temperature of 65° C. for 4 h. After the reaction was completed, a crude reaction product was obtained, ethanol in an amount of 8 times the mass of the crude reaction product was added, the mixture was filtered, a filter cake was taken, and it was dried at a temperature of 60° C. for 18 h to obtain a modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at 95°C, mixing evenly and then cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 3, adding n-butyraldehyde dropwise at 20°C for 20 min, reacting at room temperature for 3 h, heating to 50°C at a heating rate of 10°C / h after the reaction, and continuing the reaction for 1 h. After the reaction is completed, adding 5 wt% aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, adding 8 times the mass of the filter cake to wash, and drying at 60°C for 20 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 80:800:52; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ammonium cerium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added, and the mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ammonium cerium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 10:9:22:0.35:1.2, and the mixture was reacted in a nitrogen atmosphere at a temperature of 30 ° C for 20 hours. After the reaction was completed, the filter was filtered, the filter cake was taken, 10 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 60 ° C for 20 hours to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:6 at a temperature of 65° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.5 ml / h, the spinning voltage being 20 kV, the receiving distance being 20 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 20 μm; The preparation of β-cyclodextrin / polytetramethylene ether glycol complex is the same as that in Example 1; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 80°C for 20 minutes, 1,4-butanediol was added, and the mixture was reacted at 85°C for 1 hour. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 80°C for 1 hour. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 13%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 10:10:12:0.55:0.5:15:2:1.2; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent is completely evaporated, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 3 MPa and a temperature of 80°C for 3 minutes to obtain a moisture-permeable layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0032] Comparative Example 1 This comparative example discloses a method for preparing a layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 10.8:100 at room temperature for 10 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3 ml / h, the spinning voltage was 30 kV, and the receiving distance was 15 cm. After electrospinning, a polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 40 ° C for 3 hours to obtain an inner layer fabric with a thickness of 40 μm. Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol complex at a mass ratio of 100:2 at a temperature of 60° C. to obtain a spinning solution of the intermediate layer material, injecting the spinning solution of the intermediate layer material into a syringe of an electrospinning device, using the inner layer fabric as a receiving screen, spinning the spinning solution through an electrospinning instrument at room temperature, the propulsion speed of the intermediate layer material spinning solution being 1.0 ml / h, the spinning voltage being 15 kV, the receiving distance being 15 cm, and obtaining an intermediate layer / inner layer composite fabric after electrospinning; Among them, in the middle layer / inner layer composite fabric, the thickness of the middle layer fabric is 30 μm; The preparation of β-cyclodextrin / polytetramethylene ether glycol complex is the same as that in Example 1; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 70°C for 30 minutes, 1,4-butanediol was added, and the mixture was reacted at 75°C for 2 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 70°C for 2 hours. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 10%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 8:8:10:0.5:0.3:10:1.8:1; Step (3), laying the middle layer / inner layer composite fabric flat and air-drying until the solvent is completely evaporated, covering the outer layer fabric on the side with the middle layer, and hot pressing at a pressure of 2 MPa and a temperature of 70°C for 4 minutes to obtain a layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0033] Comparative Example 2 This comparative example discloses a method for preparing a layered composite fabric, comprising the following steps: Step (1), polyvinylidene fluoride, antibacterial agent, and N,N-dimethylacetamide are stirred and mixed at a mass ratio of 10:0.8:100 at room temperature for 10 hours to obtain a spinning solution of the inner layer material; The inner layer material spinning solution was injected into the syringe of the electrospinning equipment, and the roller was covered with glossy paper as a receiving screen. The inner layer material spinning solution was spun by the electrospinning instrument at room temperature. The propulsion speed of the inner layer material spinning solution was 3 ml / h, the spinning voltage was 30 kV, and the receiving distance was 15 cm. After electrospinning, an antibacterial polyvinylidene fluoride fiber membrane was obtained, which was vacuum dried at 40 ° C for 3 hours to obtain an inner layer fabric with a thickness of 40 μm. The antibacterial agent is prepared by the following steps: S11, the preparation of epoxy nanosilver is the same as that in Example 1; S12, mixing and dissolving polyvinyl alcohol and dimethyl sulfoxide at 90° C., adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and 10 wt % sodium hydroxide aqueous solution, wherein the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and 10 wt % sodium hydroxide aqueous solution is 100:180:1.8:1:8, and reacting at 55° C. for 5 h. After the reaction is completed, a crude reaction product is obtained, ethanol 5 times the mass of the crude reaction product is added, and the mixture is filtered, and the filter cake is taken and dried at 50° C. for 24 h to obtain modified polyvinyl alcohol; S13, mixing the modified polyvinyl alcohol with water at 90° C., mixing evenly, and cooling to room temperature, adding 1 mol / L aqueous hydrogen chloride solution to adjust the pH value to 2, adding n-butyraldehyde dropwise at 15° C. for 10 min, reacting at room temperature for 2 h, heating to 45° C. at a heating rate of 8° C. / h after the reaction, and continuing the reaction for 2 h. After the reaction, adding 5 wt % aqueous sodium hydroxide solution to neutralize to neutrality, filtering, taking the filter cake, washing with water 5 times the mass of the filter cake, and drying at 50° C. for 24 h to obtain modified polyvinyl butyral; The mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 75:750:48; S14, the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution were mixed in a nitrogen atmosphere, and ceric ammonium nitrate and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt were added. The mass ratio of the modified polyvinyl butyral, ethanol, 0.01mol / L nitric acid aqueous solution, ceric ammonium nitrate, and 3- [N, N-dimethyl- [2- (2-methylprop-2-enoyloxy) ethyl] ammonium] propane-1-sulfonic acid inner salt was 8: 8.5: 18: 0.3: 1. The mixture was reacted in a nitrogen atmosphere at a temperature of 25 ° C for 24 hours. After the reaction was completed, the filter was filtered, the filter cake was taken, 5 times the mass of the filter cake was added for washing, and the filter cake was dried at a temperature of 50 ° C for 24 hours to obtain an antibacterial agent; Step (2), standing the epoxy resin / waterborne polyurethane composite material for degassing, casting it into a film at a temperature of 60°C, and drying it to obtain an intermediate layer fabric with a thickness of 30 μm; The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, and N,N-dimethylformamide were mixed in a nitrogen atmosphere at 70°C for 30 minutes, 1,4-butanediol was added, and the mixture was reacted at 75°C for 2 hours. After the reaction, epoxy resin E-44 was added, and the mixture was further reacted at 70°C for 2 hours. After the reaction, toluene was added for dilution to obtain an epoxy resin / waterborne polyurethane composite material with a solid content of 10%; the mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dimethylolpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol, and epoxy resin E-44 was 8:8:10:0.5:0.3:10:1.8:1; Step (3), stacking the outer layer fabric, the middle layer fabric, and the inner layer fabric in sequence, and hot pressing them at a pressure of 2 MPa and a temperature of 70°C for 4 minutes to obtain a layered composite fabric; The preparation of the outer layer fabric is the same as that in Example 1.
[0034] In the above examples and comparative examples: polyvinylidene fluoride was obtained from Akema Co., Ltd. of France, with the brand name PVDF Kynar 741; nanosilver was obtained from Hubei Xinyuhong Biopharmaceutical Technology Co., Ltd., with a particle size of 80 nm; polyvinyl alcohol was obtained from Sinopharm Chemical Reagent Co., Ltd., with the model name polyvinyl alcohol 1788; 3-chloro-2-hydroxypropyltrimethylammonium chloride was obtained from Shanghai Aladdin Biochemical Technology Co., Ltd., with the CAS number 3327-22-8; and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt was obtained from Shanghai MacLean Biochemical Technology Co., Ltd. , CAS number: 3637-26-1; polytetramethylene ether glycol is from Shanghai MacLean Biochemical Technology Co., Ltd., with a molecular weight of 1800; polyethylene glycol is from Sigma-Aldrich, with a molecular weight of 1000; epoxy resin E-44 is from Baling Petrochemical Company, brand epoxy resin E-44; β-cyclodextrin is from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS number: 7585-39-9; polyester fabric is commercially available polyester woven fabric; water repellent, penetrant, cross-linking agent, and softener are all from NANO-TEX, among which the water repellent is fluorine-free waterproofing agent NT-X018.
[0035] Test example The performance of the layered composite fabrics prepared in the examples and comparative examples was tested, and the specific results are shown in Table 1: Table 1
[0036] Among the various indicators in Table 1: the antibacterial rate is determined with reference to GB / T 20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method", in which Escherichia coli is selected as the bacterial species; the water vapor permeability is determined with reference to GB / T 12704-2009 "Textiles - Test method for water vapor permeability - Part 1: Moisture absorption method"; the hydrostatic pressure is determined with reference to GB / T 4744-2013 "Textiles - Testing and evaluation of water repellency"; and the breaking strength is determined with reference to GB / T 3923-2013 "Textiles - Tensile properties of fabrics - Part 1: Determination of breaking force and elongation - Strip method".
[0037] According to the test results in Table 1, it can be seen that the layered composite fabric prepared by the present invention has excellent waterproof and moisture permeability, and good mechanical properties and antibacterial properties.
[0038] The present invention produces an antibacterial agent containing multiple antibacterial components including nanosilver, quaternary ammonium salt, and sulfobetaine. Due to the synergistic effect of the components in the antibacterial effect, the obtained antibacterial agent has excellent antibacterial properties. After the antibacterial agent is mixed with polyvinylidene fluoride and electrospun, the obtained inner layer fabric has good mechanical properties and antibacterial properties. In comparative example 1, no antibacterial agent is added to the inner layer material, and the antibacterial rate of the layered fabric is reduced, so the antibacterial performance of comparative example 1 is lower than that of the embodiment. In the middle layer / inner layer composite fabric prepared by the present invention, the epoxy resin / waterborne polyurethane composite material has good hydrophilicity due to the presence of hydrophilic groups, can adsorb and release water molecules, and improve the moisture conductivity and moisture permeability of the layered composite fabric; the β-cyclodextrin / polytetramethylene ether glycol complex is prepared by compounding β-cyclodextrin and polytetramethylene ether glycol. The lipophilic group dimethylene of polytetramethylene ether glycol can form a strong interaction with the hydrophobic inner cavity of β-cyclodextrin, and the hydroxyl group can form an interaction with the hydrophilic external hydroxyl group of β-cyclodextrin, so polytetramethylene ether glycol has a good modification effect on β-cyclodextrin, and the prepared β-cyclodextrin / The polytetramethylene ether glycol complex has good compatibility with the epoxy resin / waterborne polyurethane composite material; and the hydroxyl groups and ether oxygen bonds of the β-cyclodextrin / polytetramethylene ether glycol complex can also provide more channels and adsorption points for water molecules to enter the intermediate layer material, further improving the hydrophilicity, moisture conductivity and moisture permeability of the intermediate layer material; in Comparative Example 2, no β-cyclodextrin / polytetramethylene ether glycol complex is added to the intermediate layer fabric, and the intermediate layer fabric does not use electrostatic spinning, but adopts a casting method to prepare the film. The intermediate layer electrostatic spinning fiber membrane structure and the β-cyclodextrin / polytetramethylene ether glycol lack the effect of improving the moisture conductivity and moisture permeability, so the moisture permeability of Comparative Example 2 is lower than that of the embodiment.
[0039] While embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions, and variations may be made to these embodiments without departing from the principles and spirit of the invention, and that the scope of the invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a moisture-permeable layered composite fabric, characterized in that: The following steps are involved: Step (1), mixing polyvinylidene fluoride, an antibacterial agent, and N,N-dimethylacetamide to obtain a spinning solution for the inner layer material; electrospinning the spinning solution for the inner layer material to obtain an antibacterial polyvinylidene fluoride fiber membrane, and drying to obtain an inner layer fabric; Wherein, the antibacterial agent is prepared by the following steps: S11, dissolving polyvinyl alcohol and dimethyl sulfoxide, adding 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver and sodium hydroxide aqueous solution, reacting, adding ethanol after the reaction, filtering and drying to obtain modified polyvinyl alcohol; S12, uniformly mixing the modified polyvinyl alcohol and water, adding a regulator to adjust the pH value, dropping n-butyraldehyde, reacting after the dropping is complete, neutralizing, filtering, washing, and drying to obtain modified polyvinyl butyral; S13, mixing modified polyvinyl butyral, ethanol, and nitric acid aqueous solution, adding cerium ammonium nitrate and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt, reacting, filtering, washing, and drying after the reaction is completed to obtain an antibacterial agent; Step (2), mixing and stirring the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol composite to obtain a spinning solution of the intermediate layer material, and electrospinning the spinning solution of the intermediate layer material to obtain an intermediate layer / inner layer composite fabric; Step (3), covering the middle layer side of the middle layer / inner layer composite fabric with the outer layer fabric, and heat pressing to obtain a moisture permeable layered composite fabric.
2. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: In the step (1), the mass ratio of polyvinylidene fluoride, antibacterial agent and N,N-dimethylacetamide is 10-13:0.8-1.2:100; the electrospinning operation comprises: injecting the inner layer material spinning solution into the syringe of the electrospinning device, covering the roller with glossy paper as a receiving screen, spinning through the electrospinning instrument at room temperature, the inner layer material spinning solution is pushed at a speed of 3-4 ml / h, the spinning voltage is 30-35 kV, and the receiving distance is 15-20 cm; the thickness of the inner layer fabric is 30-40 μm.
3. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: When the antibacterial agent is prepared in step (1), the epoxy nanosilver in S11 is prepared by the following steps: Mix γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water and ethanol, add a regulator to adjust the pH value, add nanosilver, react, and after the reaction is completed, filter, wash and dry to obtain epoxy nanosilver; The mass ratio of γ-(2,3-epoxypropoxy)propyltrimethoxysilane, water, ethanol and nanosilver is 0.6-0.8:100-150:80-90:10; the reaction conditions are: reacting at a pH value of 4-5 and a temperature of 40-50° C. for 3-5 hours.
4. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: When preparing the antibacterial agent in step (1), in S11, the mass ratio of polyvinyl alcohol, dimethyl sulfoxide, 3-chloro-2-hydroxypropyltrimethylammonium chloride, epoxy nanosilver, and sodium hydroxide aqueous solution is 100:180-200:1.8-2:1-1.5:8-10, and the sodium hydroxide aqueous solution is a 10wt% sodium hydroxide aqueous solution; and the reaction conditions are: reacting at a temperature of 55-65°C for 4-5h.
5. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: When preparing the antibacterial agent in step (1), in S12: the mass ratio of modified polyvinyl alcohol, water and n-butyraldehyde is 75-80:750-800:48-52; the conditions for adding n-butyraldehyde are: adding at a pH of 2-3 and a temperature of 15-20°C for 10-20 minutes; the reaction conditions are: reacting at room temperature for 2-3 hours, and after the reaction is completed, heating to 45-50°C at a heating rate of 8-10°C / h, and continuing the reaction for 1-2 hours.
6. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: When preparing the antibacterial agent in step (1), in S13: the mass ratio of modified polyvinyl butyral, ethanol, nitric acid aqueous solution, cerium ammonium nitrate, and 3-[N,N-dimethyl-[2-(2-methylprop-2-enoyloxy)ethyl]ammonium]propane-1-sulfonic acid inner salt is 8-10:8.5-9:18-22:0.3-0.35:1-1.2, and the nitric acid aqueous solution is 0.01 mol / L nitric acid aqueous solution; the reaction conditions are: reacting in a nitrogen atmosphere at a temperature of 25-30° C. for 20-24 hours.
7. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: In the step (2), the mass ratio of the epoxy resin / aqueous polyurethane composite material and the β-cyclodextrin / polytetramethylene ether glycol composite material is 100:2-6; the electrospinning operation comprises: injecting the spinning solution of the intermediate layer material into a syringe of the electrospinning device, using the inner layer fabric as a receiving screen, spinning through the electrospinning instrument at room temperature, the propulsion speed of the spinning solution of the intermediate layer material is 1.0-1.5 ml / h, the spinning voltage is 15-20 kV, and the receiving distance is 15-20 cm; in the intermediate layer / inner layer composite fabric, the thickness of the intermediate layer fabric is 20-30 μm.
8. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: In step (2): The epoxy resin / waterborne polyurethane composite material is prepared by the following steps: Mix polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dihydroxymethylpropionic acid, stannous isooctanoate, and N,N-dimethylformamide, add 1,4-butanediol, and react. After the reaction is completed, add epoxy resin E-44 and continue to react. After the reaction is completed, add a diluent to dilute, and obtain an epoxy resin / waterborne polyurethane composite material; The mass ratio of polytetramethylene glycol, polyethylene glycol, diphenylmethane diisocyanate, 2,2-dihydroxymethylpropionic acid, stannous isooctanoate, N,N-dimethylformamide, 1,4-butanediol and epoxy resin E-44 is 8-10:8-10:10-12:0.5-0.55:0.3-0.5:10-15:1.8-2:1-1.2; the mixing conditions are: mixing for 20-30 minutes at a temperature of 70-80°C in a nitrogen atmosphere; the reaction conditions are: reacting for 1-2 hours at a temperature of 75-85°C in a nitrogen atmosphere; the continued reaction conditions are: continuing to react for 1-2 hours at a temperature of 70-80°C in a nitrogen atmosphere; the solid content of the epoxy resin / waterborne polyurethane composite material is 10-13%; The β-cyclodextrin / polytetramethylene glycol complex is prepared by the following steps: The β-cyclodextrin and N,N-dimethylacetamide are mixed, polytetramethylene glycol is added, and the mixture is stirred and treated. After the treatment, the mixture is dried, washed, and filtered to obtain a β-cyclodextrin / polytetramethylene glycol complex. The mass ratio of β-cyclodextrin to N,N-dimethylacetamide is 1:4; the molar ratio of β-cyclodextrin to polytetramethylene ether glycol is 1:0.5-1; and the stirring treatment conditions are: stirring treatment at room temperature for 1-2 hours.
9. The method for preparing a moisture-permeable layered composite fabric according to claim 1, characterized in that: In step (3), the hot pressing conditions are: hot pressing for 3-4 minutes at a pressure of 2-3 MPa and a temperature of 70-80°C; the outer layer fabric is made of a gram weight of 120-160 g / m 2 The polyester fabric is prepared after waterproof finishing; the finishing operation includes: dipping the polyester fabric into a waterproof finishing agent, the bath ratio is 1:20-30, the dipping time is 20-30 minutes, one dipping and one rolling, the rolling rate is 60-70%, after dipping, drying at 90-100 DEG C for 3-5 minutes, baking at 150-160 DEG C for 2-3 minutes, and obtaining an outer layer of fabric; the waterproof finishing agent is prepared by mixing a water repellent, a penetrant, a cross-linking agent, a softener, and water in a mass ratio of 5-6:0.1-0.15:1.5-2:8-10:
100.
10. A moisture permeable layered composite fabric prepared by the method for preparing a moisture permeable layered composite fabric according to any one of claims 1 to 9.
Citation Information
Patent Citations
Waterproof moisture-permeable composite fabric
CN109591406A
Cited By
Antibacterial moisture-absorption breathable pure cotton fabric, preparation method and application in non-sensitization underwear
CN120680765A